Frequency and risk factors of surgical site infections in general surgery ward of a tertiary care hospital of Karachi, Pakistan - Bibi, Safia; Channa, Ghulam Asghar; Siddiqui, Taranum Ruba; Ahmed, Waquaruddin (International Journal of Infection Control, 2011)
To aim of this study was to determine the frequency of surgical site infections and to identify the associated risk factors in general surgery ward of a tertiary care hospital of Karachi. This was a one year cross sectional study conducted in a surgical ward of Jinnah Postgraduate Medical Centre, Karachi. During the study period data was collected on a predesigned questionnaire for all the patients who underwent surgery in the general surgery ward of JPMC and patients were followed for up to 30 days for developments of surgical site infection. Infected cases were identified using CDC, USA definition for Surgical site infections. In total of 1139 patients surgical procedures were performed in the selected ward during the study period, of which 19 dropped out from the study; of the remaining 1120 patients 82 (7.3%) patients developed surgical site infection. Incidence of surgical site infections was higher in emergency procedures (13.1%) as compared to elective procedures (2.9%). Incidence related to clean, clean contaminated, contaminated and dirty procedures was 1.5%, 2.5%, 6.5% and 21.5% respectively. Age, wound class, electivity of procedure and diabetes were identified as the main contributing factors towards the development of surgical site infections. Ten patients were readmitted in the hospital after discharge due to SSI. Frequency of SSI in surgical ward of JPMC was lower than other public sector hospitals reported from Pakistan but was much higher as compared to developed countries.